Recent Inflationary Trends in World Commodities Markets - Krichene, Noureddine (Washington, D.C. : International Monetary Fund, 2008)
Expansionary monetary policies in key industrial countries and sharply depreciating U.S. dollar exchange rate sent commodities prices soaring at unprecedented rates during 2003-2007. Food prices rose to alarming levels threatening malnutrition and food riots. In contrast, consumer price indices, a leading indicator for monetary policy, were showing almost no inflation and posed a price puzzle insofar their evolution was not responsive to record low interest rates, double digit commodities inflation, and sharp exchange rate depreciation. Commodities prices were shown to be driven by one common trend, identified as a monetary shock. Policy makers may have to face a policy dilemma: maintain monetary policy stance with accelerating commodities price inflation, subsequent world recession, and financial disorder; or tighten monetary policy with subsequent world recession followed by recovery and financial and price stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet